Faulty Foundations: Soviet Economic Policies, 1928-1940 - Holland Hunter, Janusz M. Szyrmer (Princeton University Press, 2014)
SOME PROJECTS come to quick fruition, but this one has had a long gestation period. Intuitive hypotheses and preliminary empirical tests have been revised and extended, over a period of almost thirty years, to culminate in the present study. Meanwhile, developments in the USSR itself have exposed defects in the economy that were not initially so evident and have tended to support the implications of the research. Work like this is never finished, but we hope that the present stage of the study offers a coherent and persuasive evaluation of the essential features of the period from 1928 to 1940 in Soviet economic history. If so, it should help in pinpointing defective aspects of the economic system and thus in suggesting features that need replacement. We are very grateful for financial support from several sources, especially the Faculty Research Fund of Haverford College. It is not easy for small liberal-arts colleges to subsidize faculty research, and Haverford's steadfast efforts deserve recognition. Outside support began with a John Simon Guggenheim Memorial Fellowship in 1959- 60 and continued under a Brookings Institution Research Professorship in 1962-63. The next stage was supported by a National Science Foundation grant in 1969-70. Further support came from the National Council for Soviet and East European Research in 1979-80 and again in 1986. Important supplementary grants came from the American Philosophical Society. Finally, a second grant from the National Science Foundation in 1987-88, together with continued help from Haverford College, permitted completion of the study. In addition, stimulating and friendly quarters for the research have been provided by the Russian Research Center at Harvard University, the W. Averell Harriman Institute at Columbia University, and the Center for Soviet and East European Studies at the University of Pennsylvania. Permission to draw on previously published papers has been granted by Economic Development and Cultural Change, for "Optimum Tautness in Developmental Planning" (July 1961); by Basil Blackwell for "Priorities and Shortfalls in Prewar Soviet Planning," in Jane Degras and Alec Nove, eds., Soviet Planning (1964); by Slavic Review for "The Overambitious First Soviet Five-Year Plan" (June 1973); by Cambridge University Press for "A Test of Five-Year Plan Feasibility" in Judith Thornton, ed., Economic Analysis of the Soviet- Type System (1976); by MIT Press for "The New Tasks of Soviet Planning in the Thirties," in Padma Desai, ed., Marxism, Central Planning, and the Soviet Economy (1983); and by Slavic Review for "Soviet Agriculture with and without Collectivization, 1928-1940" (Summer 1988), and "Testing Early Soviet Economic Alternatives" (Summer 1991). Passages from these papers underlie sections of chapters 4 through 6, 9, 11, and 13. Our references to the works of Lenin and Stalin select, from numerous extant editions, the Russian and English versions conveniently available to us.